Application of Multicultural Education in Strengthening Community Solidarity in Indonesia - Abdullah, Anzar; Alim, Andi; Andriyadi, Fauza; Burga, Muhammad Alqadri (Jurnal Ilmiah Peuradeun, 2023)
This study aims to describe the models, methods and approaches used in multicultural education in Indonesia. The research method used is systematic literature-based qualitative research, namely an approach that manages data by reducing data, presenting, and verifying, as well as concluding data, not using mathematical calculations and statistics. The results of the research found that, first, multicultural education is very important to be implemented in Indonesia, because the community is multi-ethnic and consists of various ethnicities, religions, cultures and regional languages. Second, the models, methods and approaches that are suitable for implementing multicultural education in Indonesia are inclusive education models through cooperative learning and role-playing methods and approaches. The study concludes that multicultural education in Indonesia is very important to be implemented through the integration of inclusivism values ​​to students through classroom interaction using cooperative learning and role-playing.